Model of Systematic Assessment of Competitiveness in Branches of Economics. Its Application in the Food Sector - Dubinas, Valentinas; Stonkuviene, Renė (Ekonomika, 2005)
Assessment of competitiveness in different branches of economy still remains to be a problem both in theory and in practice. The earlier introduced models were either too complicated to implement or did not meet the management objectives based on strategic marketing. Competitiveness in the authors’ model is measured by economic indicators, since they enable to assess most accurately the competitiveness of any kind of production. Though the present model is based on the food sector, it may be successfully used in other branches of economy. The results presented in the paper may be applied for developing short- or long-term strategies in the food sector.